2019
DOI: 10.1017/s1431927619014557
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal Variation of the Intraepithelial Gland in Camel Epididymis with Special Reference to Autophagosome

Abstract: The key role of the epididymis is contributing to sperm storage, maturation, and survival. The epididymis of camel has a unique structure called the intraepithelial gland. The present work aimed to investigate the structure of the epididymal intraepithelial gland with special references to the seasonal variation. The samples were collected from the distal part of the corpus epididymes of completely healthy mature camels (Camelus dromedarius) in the breeding and nonbreeding seasons. Tomato lectin-positive mater… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 48 publications
1
13
0
Order By: Relevance
“…Data from experimental groups were statistically analyzed using one-way ANOVA with Tukey's post hoc multiple comparisons tests using the GraphPad Prism software version 5 (San Diego, CA, USA). p < 0.05 was used to define statistically significant differences between the groups [26].…”
Section: Discussionmentioning
confidence: 99%
“…Data from experimental groups were statistically analyzed using one-way ANOVA with Tukey's post hoc multiple comparisons tests using the GraphPad Prism software version 5 (San Diego, CA, USA). p < 0.05 was used to define statistically significant differences between the groups [26].…”
Section: Discussionmentioning
confidence: 99%
“…Unlike the observed changes in autophagy in the testes, compared with MD, the number of LC3 puncta and the protein expression of LC3 in the epididymides increased under both SD and LD conditions, indicating that the autophagy levels in the epididymis increased under both SD and LD. Studies have shown that the level of autophagy in the epididymides of camels significantly increases in the winter under SD (Abdel‐Maksoud, Hussein, & Attaai, 2019). The present study found similar results.…”
Section: Discussionmentioning
confidence: 99%
“…The animals were sacrificed in Bani Adie slaughterhouse in Assiut province, Egypt, according to the local ethical board guidelines of Egyptian slaughterhouses. The epididymis was carefully dissected from the testis; the specimens were taken from the distal part of corpus epididymis and immediately fixed in 4% paraformaldehyde in 0.1 M phosphate-buffered saline (PBS, pH 7.4) overnight (ON) at 4°C [as discussed in our previous study (Abdel-Maksoud et al, 2019 b )].…”
Section: Methodsmentioning
confidence: 99%